Developmental Sequela for Sexual Homicide: Testing an Integrated Multi-Theoretical Model - Chopin, Julien (Journal of interpersonal violence, 2023)
Research focusing on the role of adverse childhood experience (ACE) of individuals involved in sexual homicide (SH) is scarce. Theoretical models of SH have postulated a connection between these adverse experiences and the development of internal risk factors. However, such assumptions have never been empirically tested. Therefore, the current research aims to identify how ACEs affect the development of personality disorders and problematic behaviors during adolescence, which constitute internal risk factors for the commission of SH. The sample comes from a database including 613 individuals involved in sexual crimes in Canada among which 60 committed a SH. Bivariate and multiple regression analyses were conducted to identify personality disorders and problematic behaviors during adolescence associated with the presence of ACEs. Next, path analysis was used to identify the direct and indirect relationships between ACEs, internal risk factors, and the commission of SH. Results showed that individuals who experienced ACEs were more likely to develop internal risk factors involved in the commission of SH. Moreover, findings suggest that the impact of these adverse experiences will differ, depending on whether the child has been victim of violence or if he/she has witnessed it.